Discovering the power of Discord: Members’ experiences and their performances in learning English - Sufi, M. Iqbal Farabi; Afrida, Nina; Meutia, Cut Intan; Daulay, Sholihatul Hamidah (Universitas Islam Malang, 2024)
Discord has experienced a recent surge in its utilization for educational purposes. Numerous communities have embraced Discord servers as a means to foster and support learning activities. Many studies discuss Discord in learning English, but there is a lack of extensive academic research focusing on a member’s experiences in using Discord. Most studies on broader online language learning communities and other digital platforms, but only a few studies investigate Discord application from an overview of this phenomenon, this study aimed to determine how the members’ experience in using the Discord application as contributed to facilitating English learning and to describe the performances of Discord in fostering English. a qualitative method with a phenomenological study applied in this research. twenty members who have been using Discord for a year and more than a year and are interested in learning English became the sample by purposive random sampling. Data was gathered from unstructured interviews and participant observation online. The results from the observation demonstrated that the efficacy of Discord can be seen from the function of features, it supports English online learning through seven crucial features that users can leverage: voice channels, text channels, direct messages, screen sharing, resource sharing, bot integrations, and notifications and reminders. Data from the interview showed members’ experiences said Discord can help them in mastering English. As a result, the implications of the research can guide the development of more effective, engaging, and inclusive Discord-based learning communities, ultimately enhancing the overall learning experience and outcomes for participants.